ULTRASOUND-ASSISTED EXTRACTION AND CHARACTERIZATION OF OIL FROM BRAZIL NUT (Bertholletia excelsa HBK) - Iara Schons, Jessica; Patel Fiori, Karol; Brito Ribeiro, Elton; Regina Andrighetti, Carla; Nogueira, Roberta; Sousa Valladao, Denia Mendes de [UNESP] (Interciencia, 2017)
Brazil nut (Bertholletia excelsa H.B.K.) is a characteristic seed of the Amazon biome, rich in unsaturated fatty acids with applications in the cosmetic and alimentary area. The aim of this study was to obtain and verify the quality of the oil extracted by ultrasound. The oil was extracted with hexane on ultrasound for 2h at 45kHz. Humidity, ashes, refractive index, acidity, saponification index, peroxide index, oleic acid, density and iodine index were evaluated. The fatty acid profile was analyzed by gas chromatography, and total phenolic compounds by UV-VIS spectrophotometry. The extraction yield was of 37,38% and the results of the evaluated parameters showed good quality of the obtained oil. As for the fatty acid chemical composition, a high percentage (similar to 68,72%) of unsaturated fatty acid was observed. The oil also showed a relevant total phenolic compound content. The results obtained were comparable to those obtained by pressing and Soxlhet, demonstrating the extraction efficiency, besides using reduced amounts of reagents. The proposed method for obtaining Brazil nut oil using ultrasonic assisted extraction was simple, fast and inexpensive.